Preparation of water samples for proficiency testing on radionuclides. (September 2015) - Polkowska-Motrenko, H.; Fuks, L.; Kalbarczyk, P.; Dudek, J.; Kulisa, K.; Oszczak, A.; Zuba, M.
Abstract: The Institute of Nuclear Chemistry and Technology (INCT) procedure for preparation of water samples for proficiency testing on determination of 241 Am, 137 Cs, 239 Pu, 226 Ra and 90 Sr in water is presented. Natural waters were applied as the raw materials and spiked with the aforementioned radionuclides. The procedure of spiking water allows to prevent losses of the radionuclides and to assign property values from formulation. The main advantages of this procedure are (i) similarity of the test materials to the water samples routinely analysed by radioanalytical laboratories, and (ii) traceable assigned values with low uncertainties. Highlights: By participating in PTs the radiochemical laboratories demonstrate their competence. Test materials should be homogeneous, stable, provide proper values. Water used as test material should contain low self-activity and proper salt content. The procedure allows to obtain homogeneous, stable materials with a desired activity.